2022
DOI: 10.1002/ehf2.13974
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in efficacy of pharmacological therapies in heart failure with reduced ejection fraction: a meta‐analysis

Abstract: Aims Recent studies have suggested potential sex differences in treatment response to pharmacological therapies in heart failure (HF). We performed a systematic review and meta-analysis of studies comparing treatment effects between men and women with HF and reduced ejection fraction (HFrEF) using established guideline-directed medical therapy and other emerging pharmacological treatments. Methods and results Systematic search was performed on PubMed, Embase, and Cochrane Library for randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…91–93 However, a recent meta-analysis of 5 RCTs concerning the role of beta-blockers in HF patients, showed no gender difference in treatment effect between males and females for the outcome of all-cause mortality and the composite of death or HF hospitalization. 85 The same results have also been shown in a European observational registry, wherein beta-blockers had a comparable effect in both sexes in reducing all causes of death and HF hospitalization. Importantly, similar to ACE-I, women needed lower doses of beta-blockers than males (50–60% of the target doses) to achieve the same reduction of the outcomes.…”
Section: Pharmacodynamic and Pharmacokinetic Differences In The Elderlysupporting
confidence: 64%
See 1 more Smart Citation
“…91–93 However, a recent meta-analysis of 5 RCTs concerning the role of beta-blockers in HF patients, showed no gender difference in treatment effect between males and females for the outcome of all-cause mortality and the composite of death or HF hospitalization. 85 The same results have also been shown in a European observational registry, wherein beta-blockers had a comparable effect in both sexes in reducing all causes of death and HF hospitalization. Importantly, similar to ACE-I, women needed lower doses of beta-blockers than males (50–60% of the target doses) to achieve the same reduction of the outcomes.…”
Section: Pharmacodynamic and Pharmacokinetic Differences In The Elderlysupporting
confidence: 64%
“… 84 These data have further been confirmed in a recent meta-analysis from 7 RCTs showing no difference in the ACE-I or ARB's treatment between sex in all-cause mortality and the combined outcome of mortality and HF hospitalization. 85 HF guidelines recommend up-titration of these drugs to the same target dose in both sexes. However, two post-doc analyses from the HEAAL 86 and ATLAS 87 studies have shown that a lower dosage in women was equally effective compared to higher dosages.…”
Section: Pharmacodynamic and Pharmacokinetic Differences In The Elderlymentioning
confidence: 99%
“…In the PARADIGM-HF trial, only 21.8% of patients enrolled were women. However, ARNI therapy was shown to reduce cardiovascular mortality and heart failure hospitalizations in both men and women (HR 0.80, 90.72-0.90; HR 0.77, 0.62-0.95, respectively; p = 0.63) (212). A previous prospective registry in 10 centers examined sex differences in efficacy, safety, and tolerability of sacubitril-valsartan and found no difference in discontinuation of ARNI therapy, no difference in received dose, and no difference in adverse events between women and men.…”
Section: Angiotensin Receptor-neprilysin Inhibitionmentioning
confidence: 98%
“… 13 , 14 , 15 , 16 , 17 Newly emerging therapies such as the soluble guanylate cyclase stimulators and cardiac myosin activators in the V er ic igua t Gl o bal Study in Subjects With Heart Failure With R educed Eject i on Fr a ction (VICTORIA)-HF and G lobal A pproach to L owering A dverse C ardiac Outcomes T hrough I mproving C ontractility in H eart F ailure (GALACTIC-HF) trials respectively, showed no sex-based differences in heart failure hospitalizations or CV death. 18 …”
Section: Current Status and Challenges: The Influence Of Sex And Gend...mentioning
confidence: 99%